Computer-assisted sequencing, interval graphs, and molecular evolution - Jungck, John R.; Dick, Gregg; Dick, Amy Gleason (BioSystems, 1982)
In 1945, Fox developed the strategy for sequencing long proteins by using overlapping fragments. We show how the formal mathematical technique for the construction of interval graphs (Gilmore and Hoffman, 1964) is useful both pedagogically for understanding the underlying logic of sequencing linear molecules and is more amenable to automation because of its algorithmic nature. We also present a computer program, that employs the interval graph algorithm, which can be used to sequence proteins when given digest data. An example is given to illustrate all the steps involved in the algorithmic processing of the data. The need for such developments with respect to molecular evolution is discussed.